Case Report: Rare case of anterior cruciate ligament reconstruction in a 26-year-old female paraplegic patient: technical considerations and rehabilitation outcomes - Raizah, Abdullah (Frontiers in Surgery, 2025)
BackgroundAnterior cruciate ligament (ACL) injuries in paraplegic patients are rare and pose unique challenges in treatment planning. Functional knee stability is critical for rehabilitation, especially in those regaining partial mobility.Case presentationA 26-year-old female with flaccid paraplegia following polytrauma developed symptomatic right knee instability. MRI (1.5 T) confirmed a complete ACL rupture. She underwent ACL reconstruction using an 8.5 mm graft combining ipsilateral hamstring and contralateral semitendinosus tendons. Arthroscopic reconstruction was performed via an anteromedial portal, with femoral suspensory fixation and tibial bioabsorbable screw. A tailored rehabilitation program incorporating neuromuscular stimulation led to progressive improvement in quadriceps strength (MRC Grade 2–4) and gait function.ConclusionACL reconstruction can be a viable option in selected paraplegic patients with partial mobility recovery when mechanical instability impedes functional progress. This case underscores the importance of individualized surgical and rehabilitation strategies in this complex population.